An unusual case of bullae and scars - Vaidya, Tanvi P.; Bhat, Ramesh M.; Dandekeri, Sukumar (International Journal of Research in Dermatology, 2019)
The term epidermolysis bullosa (EB) encompasses a group of inherited mechano-bullous disorders, clinically characterized by blisters over skin and mucosae following minor frictional trauma. The diagnosis is predominantly clinical, but further classification is carried out by defining the histological level of the split. Histopathology tends to be ambiguous, as it was in this case. Our case is of a twelve-year-old male child who came with complaints of recurrent painful fluid filled lesions all over the body since 10 days of birth, aggravated by trauma, with exacerbations in the summer, and with a history of similar lesions in the mother and maternal uncle. On examination, there were multiple flaccid bullae, crusted erosions, scars and milia over trauma prone sites, such as the elbows, back, knees, shins and knuckles, with nail dystrophy and pitting of the teeth. The clinical impression as well as histopathology suggested a dominant dystrophic or a junctional EB, but immunofluorescence antigen mapping revealed it to be a case of EB simplex. We must thus bear in mind that histopathology is not definitive in EB, and immunofluorescence antigen mapping or transmission electron microscopy is imperative to correctly diagnose it.